2023
DOI: 10.3390/su15107853
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Toxicity of ZnO Nanoparticles on Microalgae at Different Initial Nutrient Concentrations

Abstract: The aim of this work was to investigate the combined short-term toxic effect of zinc oxide (ZnO) nanoparticles (NPs) and nitrate concentration of the medium on freshwater microalgae. For this purpose, freshwater microalgae Chlorococcum sp. was cultivated in modified Blue-Green medium (BG-11) containing nitrate concentrations ranging from 0 to 300 mg/L, and exposed to ZnO NPs in different concentrations (0.081 to 810 mg/L) for a period up to 96 h. The experimental results revealed that algal growth was affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Changes in pH values (Figure 4) were observed in all cultures, and its values increased over time. More precisely, as it has already been observed in previous studies as well, algal growth has been found to increase the pH of the culture medium [26]. This is due to the fact that cells consume diluted CO 2 during photosynthesis at a rate higher than that of the dissolution of gaseous carbon dioxide into the medium.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Changes in pH values (Figure 4) were observed in all cultures, and its values increased over time. More precisely, as it has already been observed in previous studies as well, algal growth has been found to increase the pH of the culture medium [26]. This is due to the fact that cells consume diluted CO 2 during photosynthesis at a rate higher than that of the dissolution of gaseous carbon dioxide into the medium.…”
Section: Resultssupporting
confidence: 68%
“…In previous studies by our team [17] investigating the toxic effect of ZnO NPs on Scenedesmus rubescens, an increasing tendency in the cell concentration was observed after 48 h. This might be attributed to the adaptation period of S. rubescens to new cultivation conditions. Despite the importance of nitrogen in microalgae proliferation and the fact that nitrates were the unique source of nitrogen in our experiments, nitrate availability was found to affect biomass growth in a non-linear way, as demonstrated by other studies as well [15,24,26]. Extracellular as well as intracellular parameters could be the reason for this phenomenon.…”
Section: Resultsmentioning
confidence: 40%
See 2 more Smart Citations
“…The growth process was affected by the concentration of nanoparticles and the initial nitrate content in the cultivation medium. Extreme quantities, meaning both high and low levels of nitrates, have been shown to increase the toxicity of nanoparticles [30]. Growing microalga P. purpureum CNMN-AR-02 in MM1 medium with a nitrate content of 0.17 g/L and the addition of 10 nm AgNPs at a concentration of 10 µM led to a reduction in the amount of biomass of 18.7%.…”
Section: Discussionmentioning
confidence: 99%